STRATEGI GURU DALAM PEMBIASAAN KEMANDIRIAN ANAK DI MASA PANDEMIK - Intan Kusumadewi, - (2021)
This research design uses a qualitative research method with a case study approach to see what strategies or methods are used by the teacher in habituating independence to children, especially during the Covid-19 pandemic. The purpose of this study was to find out what the teacher's strategies were in getting used to early childhood, especially during the Covid-19 pandemic. This research was conducted in two different schools and with a total of three participants. The data collection technique here uses interview techniques. For data analysis, four stages were carried out, namely data collection, data reduction, data presentation and drawing conclusions. The results of the analysis found that the habituation of independence carried out during this pandemic was not given enough attention due to limited direct contact between teachers and children. So the results show that the two schools are more focused on assessing their independence alone. For the habituation of independence, the teacher gives fully to the parents of the students. And for the strategies or methods used by the teacher for habituation of children's independence, the results obtained are three. First, the teacher habituates through online classes, then provides a checklist which will later become the teacher's guide to see the development of children's independence. Then the last one was habituation with a home visit.